ChemInform Abstract: Carbon‐Heteroatom Bond Forming Reactions and Heterocycle Synthesis under Ball Milling. Issue 25 (5th June 2015) - Ranu, Brindaban C.; Chatterjee, Tanmay; Mukherjee, Nirmalya
Abstract: Review: 66 refs.